Upaya Kelompok Wanita Tani Dalam Peningkatan Pendapatan Keluarga Melalui Pemanfaatan Lahan Pekarangan: Studi Pada Kelompok Wanita Tani Kenanga di Desa Nyanggahurip Kecamatan Cibereum Kota Tasikmalaya - Lulu Fardhilah; Yus Darusman; Adang Danial (Lifelong Education Journal, 2022)
ABSTRACT This research is motivated by the problem of poverty that is still a lot in the community and the lack of optimization of yard land where there are still many people who are not aware of the benefits of yard land in addition to making the yard beautiful it also has the potential to provide food, and reduce household spending. The purpose of this study is to help increase the income in the family. The problems that exist in the community are related to poverty and poorly functioning yards, it is necessary to form a Kenanga farmer women's group in Nyanggahurip Village, Cibereum District, Tasikmalaya City to help increase family income through the use of yard land. The method used in this study is a research method with a descriptive qualitative type of research. Researchers use data sources, data collection techniques through interviews, observation, and documentation. From the results obtained in this study the formation of a group cannot be separated from proximity, interaction, balance, continuity and exchange. By joining the women's farmer group, women are able to develop the potential that exists within themselves through the use of yard land. The existence of support from the Department of Food Security and Fisheries of the City of Tasikmalaya has made the kenanga women farmer group run well. The success of the kenanga women farmer group is also seen from the results obtained by the members of the kenanga women farmer group.